Standalone Internet speech restructuring treatment for adults who stutter: A phase I study. (3rd July 2016) - Erickson, Shane; Block, Susan; Menzies, Ross; O'Brian, Sue; Packman, Ann; Onslow, Mark
Abstract: Purpose : This Phase I trial reports the results of a clinician-free Internet speech restructuring treatment for adults who stutter. The program consists of nine phases with concepts loosely based on the Camperdown Program. Method : Twenty adults who stutter were recruited. They were given unlimited access to the program for 6 months. Primary outcome measures were the percentage of syllables stuttered and self-reported severity ratings. Result : Five participants accessed all phases of the program, while another five accessed more than half the phases. The remaining 10 accessed between one and four phases. Four of five participants who accessed all phases reduced their stuttering frequency by more than 50% and an additional two participants who accessed more than half the phases also achieved similar reductions. These results were confirmed by self-reports of stuttering severity. Stuttering reductions were largely commensurate with the amount of the program accessed. Conclusion : As with other clinician-free programs in related health areas, maintaining adherence to the program's procedures was a significant issue. Nonetheless, this novel approach to treating stuttering has the potential to be a viable alternative for some clients and may help to address the significant access and relapse issues that affect treatment provision for adults who stutter.